Public Finance in Islam. (IMF Working Papers; Working Paper, 1989)
The paper analyzes the bearing of Islamic teachings on the conduct of fiscal policy. It is shown that Islamic teachings do not prescribe any rigid system of public finance. The major emphasis is on the state's responsibility to assure at least a basic minimum standard of living for all citizens. The paper deals with issues related to evolution of fiscal policies best suited to achieve this and other Islamic socio-economic objectives in the specific framework of Islamic teachings. The implications of such a system for growth, monetary stability, resource allocation, and pattern of income distribution are also examined.